Electrical and Elastic Properties of Individual Single‐Layer Nb4C3Tx MXene Flakes. (26th February 2020) - Lipatov, Alexey; Alhabeb, Mohamed; Lu, Haidong; Zhao, Shuangshuang; Loes, Michael J.; Vorobeva, Nataliia S.; Dall'Agnese, Yohan; Gao, Yu; Gruverman, Alexei; Gogotsi, Yury; Sinitskii, Alexander
Abstract: 2D carbides and nitrides (MXenes) are widely recognized for their exceptional promise for numerous applications. However, physical property measurements of their individual monolayers remain very limited despite their importance for revealing the intrinsic physical properties of MXenes. The first mechanical and electrical measurements of individual single‐layer flakes of Nb4 C3 T x MXene, which are prepared via an improved synthetic method are reported. Characterization of field‐effect transistor devices based on individual single‐layer Nb4 C3 T x flakes shows an electrical conductivity of 1024 ± 165 S cm −1, which is two orders of magnitude higher than the previously reported values for bulk Nb4 C3 T x assemblies, and an electron mobility of 0.41 ± 0.27 cm 2 V −1 s −1 . Atomic force microscopy nanoindentation measurements of monolayer Nb4 C3 T x membranes yield an effective Young's modulus of 386 ± 13 GPa, assuming a membrane thickness of 1.26 nm. This is the highest value reported for nanoindentation measurements of solution‐processable 2D materials, revealing the potential of Nb4 C3 T x as a primary component for various mechanical applications. Finally, the agreement between the mechanical properties of 2D Nb4 C3 T x MXene and cubic NbC suggests that the extensive experimental data on bulk carbides could be useful for identifying new MXenes with improved functional characteristics. Abstract : The first electrical and mechanical measurements of individual monolayer flakes of Nb4 C3 T x MXene are reported. They show an electrical conductivity of 1024 ± 165 S cm −1, which is much higher than the previously reported values for bulk Nb4 C3 T x assemblies. Due to its high effective Young's modulus (386 ± 13 GPa), Nb4 C3 T x is a promising material for various mechanical applications.